Diffusion resistance of claddings for corrosion protection of structural alloys in molten salt reactors - Eveleigh, Cedric (My University, 2019)
Corrosion is a major challenge in the use of molten ﬂuoride salt as a coolant in molten salt reactors (MSRs). A promising way of satisfying the two requirements of high strength and corrosion resistance is to clad structural alloys with a corrosion resistant material. Four candidate cladding and structural alloy combinations—stainless steel 316L and Incoloy 800H structural alloys either diffusion bonded to Hastelloy N or electroplated with nickel—were thermally aged at 700 °C for two to eight months. Based on measured concentration profles, the diffusion resistance of the four material combinations was compared and diffusion results were extrapolated to an end of reactor lifetime. The most important conclusion from this work is that Hastelloy N is highly likely to be signifcantly more diffusion resistant than nickel. The difference in diffusion resistance between Incoloy 800H and stainless steel 316L is relatively small. Two methods were used for extrapolating experimental diffusion results: (1) a diffusion model and calculated diffusion coeffcients and (2) simulations with Thermo-Calc DICTRA. Some simulations were carried out with a corrosion boundary condition of near-zero chromium concentration, demonstrating the potential of simulations for predicting diffusionlimited corrosion in molten ﬂuoride salts. A surprising result of these simulations is that decreasing the thickness of Ni plating did not increase the thickness of diffusion zones in underlying structural alloys.
Keywords: claddings; coatings; diffusion resistance; materials durability; corrosion; molten salt reactor (MSR); nuclear reactor